Intestinal resection and primary anastomosis as treatment of intussusception due to ileum lipoma: case report and review - Blaz Zavala, Rogelio A.; Flores Garcia, Alba E.; Corona Flores, Yanetzy E.; Calderón, Uriel Cruz; Elizondo, César Reyes (International Journal of Research in Medical Sciences, 2023)
Intussusception is an unusual cause of intestinal occlusion in adults, accounting for 5% of cases, and is the result of an underlying pathology in 90% of cases, 60% of which are tumors. The pathogenesis describes the invagination of an intestinal segment into the lumen of an adjacent segment with subsequent alterations in irrigation, risk of necrosis and perforation. Surgical management is indicated in adult patients to restore intestinal transit and to exclude malignancy as the axis of the intussusception. We present the case of a 58-year-old female patient with enteric intussusception at ileum due to lipoma, who underwent bowel resection and manual end-to-end intestinal anastomosis in two planes.